Facilitating design: examining the effects of facilitator's neutrality on trust and potency in an exploratory experimental study. (8th April 2021) - Wróbel, Agata Ewa; Lomberg, Carina; Cash, Philip
Abstract: Facilitation style appears to be an important determinant of design team effectiveness. The neutrality of the group facilitator may be a key factor; however, the characteristics and impact of neutrality are relatively understudied. In a designed classroom setting, we examine the impact of two different approaches to group facilitation: (i) facilitator's neutrality expressed as low equidistance and high impartiality and (ii) facilitator's neutrality expressed as high equidistance and low impartiality, on team trust, trust to the facilitator and team potency. To do this, we conducted a repeated-measures experiment with a student sample. Our results indicate that facilitators expressing neutrality through low equidistance and high impartiality had a greater positive impact on team trust. The two approaches did not differ on team potency and facilitator trust. These results contribute to developing theories of design facilitation and team effectiveness by suggesting how facilitation may shape team trust and potency in group design. Based on our findings, we point to the need for future work to further examine the impact of facilitator's process awareness and neutrality, and show how facilitation methods may benefit teams during creative design teamwork.